Investigation of the Susceptibility of Human Cell Lines to Bovine Herpesvirus 4 Infection: Demonstration that Human Cells Can Support a Nonpermissive Persistent Infection Which Protects Them against Tumor Necrosis Factor Alpha-Induced Apoptosis - Gillet, L. (American Society for Microbiology, 2004)
Bovine herpesvirus 4 (BoHV-4) is a gammaherpesvirus that has a worldwide distribution in the population of cattle. Many factors make human contamination by BoHV-4 likely to occur. In this study, we performed in vitro experiments to assess the risk and the consequences of human infection by BoHV-4. First, by using a recombinant BoHV-4 strain expressing enhanced green fluorescent protein under the control of the human cytomegalovirus immediate-early gene promoter, we tested 21 human cell lines for their sensitivity and their permissiveness to BoHV-4 infection. These experiments revealed that human cell lines from lymphoid and myeloid origins were resistant to infection, whereas epithelial cells, carcinoma cells, or adenocarcinoma cells isolated from various organs were sensitive but poorly permissive to BoHV-4 infection. Second, by using the HeLa cell line as a model of human cells sensitive but not permissive to BoHV-4 infection, we investigated the resistance of infected cells to apoptosis and the persistence of the infection through cellular divisions. The results obtained can be summarized as follows. (i) BoHV-4 nonpermissive infection of HeLa cells protects them against tumor necrosis factor alpha-induced apoptosis. (ii) BoHV-4 infection of HeLa cells persists in cell culture; however, the percentage of infected cells decreases with time due to erratic transmission of the viral genome through cell division. (iii) BoHV-4 infection has no effect on the rate of HeLa cell division. Altogether, these data suggest that BoHV-4 could infect humans. This study also stresses the importance of considering the insidious effects of nonpermissive infection when the biosafety of animal gammaherpesviruses for humans is being considered.